Structural Changes Induced by Daily Music Listening in the Recovering Brain after Middle Cerebral Artery Stroke: A Voxel-Based Morphometry Study - Särkämö, Teppo; Ripollés, Pablo; Vepsäläinen, Henna; Autti, Taina; Silvennoinen, Heli M.; Salli, Eero; Laitinen, Sari; Forsblom, Anita; Soinila, Seppo; Rodríguez-Fornells, Antoni (Frontiers in Human Neuroscience, 2014)
Music is a highly complex and versatile stimulus for the brain that engages many temporal, frontal, parietal, cerebellar, and subcortical areas involved in auditory, cognitive, emotional, and motor processing. Regular musical activities have been shown to effectively enhance the structure and function of many brain areas, making music a potential tool also in neurological rehabilitation. In our previous randomized controlled study, we found that listening to music on a daily basis can improve cognitive recovery and improve mood after an acute middle cerebral artery (MCA) stroke. Extending this study, a voxel-based morphometry (VBM) analysis utilizing cost-function masking was performed on the acute and 6-month post-stroke stage structural MRI data of the patients (n = 49) who either listened to their favourite music (music group, n = 16) or verbal material (audio book group, n = 18) or did not receive any listening material (control group, n = 15) during the 6-month recovery period. Although all groups showed significant grey matter volume (GMV) increases from the acute to the 6-month stage, there was a specific network of frontal areas [left and right superior frontal gyrus (SFG), right medial SFG] and limbic areas [left ventral / subgenual anterior cingulate cortex (SACC) and right ventral striatum (VS)] in patients with left hemisphere damage in which the GMV increases were larger in the music group than in the audio book and control groups. Moreover, the GM reorganization in the frontal areas correlated with enhanced recovery of verbal memory, focused attention, and language skills, whereas the GM reorganization in the SACC correlated with reduced negative mood. This study adds on previous results, showing that music listening after stroke not only enhances behavioural recovery, but also induces fine-grained neuroanatomical changes in the recovering brain.